A closed-circulation system for chemical polishing of the 1.3-GHz single-cell copper cavity substrate for niobium sputtering. (23rd June 2021) - Yang, F.Y.; Dai, J.; Zhang, P.; Wang, N.; Li, Z.Q.
Abstract: A 1.3-GHz copper cavity chemical polishing system has been developed by the Institute of High Energy Physics. It has been used for the surface treatment of copper cavity substrates before the niobium sputtering. The system uses the SUBU polishing agent developed by the European Organization for Nuclear Research (CERN), which is a four-component mixed acid with a working temperature of 72 ∘ C. For environmental protection reasons, the system adopts a fully closed-cycle mode, which prevents acid volatility at high temperatures to the ambient environment. Based on the sample experiments, polishing steps have been optimized to avoid as much as possible the oxidation phenomenon which is easily introduced to the copper cavity inner surface, including cooling, dilution, and passivation process. Finally, the surface treatment process of the closed polishing system was determined based on the optimized polishing steps, and the oxygen isolation protection method after treatment was put forward to accommodate long-distance transportation of the copper cavity before coating. The experimental results show that the surface of the copper cavity after chemical polishing was smooth and bright with an average roughness of 0.12 μm.